2023
DOI: 10.1039/d3ra03028h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cyclic carbonates from CO2 cycloaddition to bio-based epoxides and glycerol: an overview of recent development

Abstract: Anthropogenic carbon dioxide (CO2) emissions contribute significantly to global warming and deplete fossil carbon resources, prompting a shift to bio-based raw materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 151 publications
1
4
0
Order By: Relevance
“…All these control experiments clearly revealed that though each of the components can catalyze the fixation on their own to a certain extent, to perform the reaction more efficiently and to improve the percentage of cyclic carbonate conversion in a short period of time under benign conditions, all the components must be used together. Thus, a positive synergistic effect between the IITKGP-40 a catalyst and cocatalyst is necessary to achieve CO 2 fixation with high conversion, and a high turnover number and this observation is in agreement with the second-order dependence on the sole TBAB toward the rate of CO 2 fixation. , …”
Section: Catalytic Performancesupporting
confidence: 80%
See 1 more Smart Citation
“…All these control experiments clearly revealed that though each of the components can catalyze the fixation on their own to a certain extent, to perform the reaction more efficiently and to improve the percentage of cyclic carbonate conversion in a short period of time under benign conditions, all the components must be used together. Thus, a positive synergistic effect between the IITKGP-40 a catalyst and cocatalyst is necessary to achieve CO 2 fixation with high conversion, and a high turnover number and this observation is in agreement with the second-order dependence on the sole TBAB toward the rate of CO 2 fixation. , …”
Section: Catalytic Performancesupporting
confidence: 80%
“…Thus, a positive synergistic effect between the IITKGP-40a catalyst and cocatalyst is necessary to achieve CO 2 fixation with high conversion, and a high turnover number and this observation is in agreement with the secondorder dependence on the sole TBAB toward the rate of CO 2 fixation. 67,68 To confirm the heterogeneous nature of the catalyst, a leaching test was performed where the reaction mixture was filtered under hot conditions to remove the active catalyst after the reaction was carried out for 3 h. Thereafter, the reaction was continued for another 3 h with the filtrate (Figure S18a). As expected, the conversion percentage of styrene oxide did not improve over the time after the removal of the catalyst.…”
Section: ■ Catalytic Performancementioning
confidence: 99%
“…We aim to provide a fine understanding of the most recent catalytic systems to either exploit the proton shuttle mechanism or the conventional pathway. The engineering of catalysts and optimization of procedures have already been extensively covered in the literature. ,, However, the mechanistic and structure–reactivity aspects of these catalytic systems are often only superficially discussed. We strongly believe that a thorough mechanistic understanding is a key driver of innovation.…”
Section: Prior Art and Scope Of This Reviewmentioning
confidence: 99%
“…CO 2 is a renewable, nonflammable, nontoxic, and readily available C1 source. , Over the years, CO 2 has been captured and utilized in a variety of ways such as conventional capture, oxyfuel capture, precombustion capture, postcombustion capture, and cryogenic CO 2 capture. In addition, CO 2 was used in the CO 2 -philes, which were further used to develop surfactants and chelating agents. Furthermore, CO 2 is an efficient C1 feedstock in the synthesis of various chemicals such as formic acid, urea, methanol, cyclic carbonates, oxazolidine, urethanes, polycarbonates, benzimidazole, quinazoline, etc. Previously, phosgene methods were used for the synthesis of benzimidazole and quinazoline, but there were so many limitations that this method is now replaced by the catalytic process. The biggest hurdle for CO 2 fixation in value-added products is kinetic inertness and thermodynamic stability. Furthermore, kinetic inertness and catalytic pathways such as homogeneous, heterogeneous, photochemical, radiochemical, electrochemical, thermochemical, and biochemical pathways have been used. Thiols, halohydrocarbons, olefins, and amines are nucleophilic and N-heterocyclic compounds that are biocompatible and used in the medical industry. In addition, they are also used in plant growth regulators. Benzimidazole and quinazoline are important N-heterocyclic compounds that are widely used as the intermediate substrates for which C–N, C–S, C–C, and C–O bonds are formed via CO 2 .…”
Section: Introductionmentioning
confidence: 99%